The Emergency of Prosociality: A Developmental Perspective on Altruism and Other Prosocial Behavior in the Face of Disaster. (December 2022) - Rose, Lucie; Dezecache, Guillaume; Powell, Tara; Chokron, Sylvie; Kovarski, Klara
No two emergency situations are alike. A combination of human and contextual factors makes each emergency and disaster unique in its time line, its aftermath, and especially its impact on affected populations. In all of these situations, however, people engage in prosocial behavior that benefits others. We provide an overview of altruistic and other prosocial behavior in typical human development and of developmental distinctions between helping, sharing, and comforting. We focus on the expression of these behaviors in emergency situations, using the COVID-19 pandemic to illustrate how prosociality shifts and adapts in a specific context. Finally, we suggest that a developmental framework may help researchers and professionals in the field achieve a more comprehensive understanding of the many facets and underlying mechanisms of prosociality in emergency contexts.